Penerapan Model Arias pada Pembelajaran Kooperatif Tipe Think-Pair-Share (TPS) dalam Meningkatkan Motivasi Belajar dan Hasil Belajar Siswa Kelas VIII MTs AlAmin Pakis - Wiwik Kusmawati; Purwaning Budi Lestari (IKIP Budi Utomo Malang, 2016)
This study aims to: (1) increase the motivation of class VIII student of MTs Al-Amin Pakis on the subject of growth and development, using the learning model of ARIAS at strategic cooperative learning Think-Pair-Share (TPS), (2) increase the yield class VIII student of MTs Al-Amin Pakis on the subject of growth and development, using ARIAS model study on cooperative learning strategies ThinkPair-Share (TPS). In this research is classroom action research (PTK/Classroom Action Research) by using a qualitative approach. The data analysis technique used to examine all the data that have been collected for researchers carrying out the practice of applying the learning model of ARIAS at learning strategies in the classroom TPS VIII through science lessons about growth and development in MTs Al-Amin Ferns. Data derived from the results of observations, interviews, tests and other data. Data analysis was performed through three steps: data reduction, a data display (presentation of data), conclusion drawing/verifcation (conclusion). Based on the analysis it can be concluded that: (1) the use of the learning model ARIAS on cooperative learning strategies Think-Pair-Share, can increase learning motivation eighth grade students of MTs Al-Amin Ferns in the subject of growth and development, (2) use ARIAS learning model on cooperative learning strategies Think-Pair-Share, can improve learning outcomes eighth grade students of MTs Al-Amin Ferns in the subject of growth and development.